The effectiveness of mindfulness-based cognitive therapy for children on anxiety, attentional control, and emotion regulation in children: a study protocol - Kholghi, Habibeh; Habibi Asgarabad, Mojtaba; Abolmaali Alhosseini, Khadijeh; Dehghani, Fahimeh; Semple, Randye J. (Frontiers in Pediatrics, 2025)
IntroductionChildhood stressors and adverse experiences can increase the likelihood of children developing mental disorders. The development of mindfulness-based cognitive therapy for children (MBCT-C) offers opportunities to improve emotional resiliency and reduce these children's vulnerabilities. The current study introduces the framework of a future clinical trial that seeks to examine the level of satisfaction and the efficacy of MBCT-C on anxiety, attentional control, and emotional regulation in children.MethodThis research protocol outlines a quasi-experimental design that compares MBCT-C with an active control group. The intervention group will participate in a 12-session MBCT-C program, while the active control group will receive a 12-session program of life skills training (LST). Eighty children aged between 8 and 12 years will be randomly assigned to the intervention or the control group. Data using the Mindful Attention Awareness Scale for Children (MAAS-C), the Emotion Regulation Checklist (ERC), the State-Trait Anxiety Inventory for Children (STAI-CH), and the Attentional Control Scale for Children (ACS-C) will be collected at three times: baseline, post-intervention, and six months following the intervention. The Mindfulness Program Satisfaction Questionnaire (MPSQ) will assess participant satisfaction with the program. The effectiveness of MBCT-C will be evaluated using a conditional mixed regression model in STATA-18.DiscussionProviding a research protocol to conduct a clinical trial on MBCT-C before the intervention phase provides a precise evaluation of the goals and hypotheses, study method, assessment tools, and treatment outcomes.